Measurement of red blood cells deformation index in a hyperbolic microchannel - Faustino, Vera (2013)
A hyperbolic microchannel was used for the purpose of observing the deformation index of the erythrocytes after contact with human tumour cell line (HCT-15 - colon carcinoma). Three cases were compared and the results showed that the deformation index decreases when erythrocytes are in contact with HCT-15.